Emotion, Authority, and Death: (Raced) Negotiations in Mock Capital Jury Deliberations. Issue 2 (11th December 2014) - Lynch, Mona; Haney, Craig
<x xml:space="preserve">Abstract</x> This article explores the role of emotion in the capital penalty‐phase jury deliberations process. It is based on the qualitative analysis of data from ninety video‐recorded four to seven person simulated jury deliberations that examined the influence of race on death sentencing outcomes. The analysis explores when and how emotions are expressed, integrated into the jury's sentencing process, and deployed in penalty‐phase decision making. The findings offer critical new insights into the role that emotion plays in influencing these legal judgments by revealing how jurors strategically and explicitly employ emotion in the course of deliberation, both to support their own positions and neutralize or rebut the opposing positions of others. The findings also shed light on the various ways that white male capital jurors utilize a panoply of powerful emotion‐based tactics to sway others to their position in a manner that often contributes to racially biased outcomes.